Analysis of Ednrb Gene Expression From Blood Samples Using Pcr As a Non-Invasive Biomarker for Early Detection and Severity Assessment of Hirschsprung Disease at Abdul Wahab Sjahranie Hospital, East Kalimantan - Pancoro Pujakelana; Yadi Yadi; Dadik Agus Soenjoto (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT This study aimed to analyze the expression of the Endothelin Receptor Type B (EDNRB) gene from peripheral blood samples of patients with Hirschsprung disease (HSCR) using the Polymerase Chain Reaction (PCR) method and to evaluate its potential as a non-invasive biomarker for early detection and clinical severity assessment. A case-control study was conducted at Abdul Wahab Sjahranie Hospital, Samarinda, East Kalimantan. Peripheral blood samples were collected from HSCR patients and healthy controls. Total RNA was extracted and complementary DNA synthesized, followed by quantitative PCR to measure EDNRB gene expression. The relative expression levels were calculated using the RQ method, and statistical analyses were performed to evaluate differences between groups and correlations with clinical severity. The expression of the EDNRB gene was significantly lower in HSCR patients compared to healthy controls (p 0.05). Receiver operating characteristic (ROC) analysis demonstrated a moderate diagnostic performance with a sensitivity of 62.5% and specificity of 70.6%. Furthermore, reduced EDNRB expression was associated with higher disease severity, although this correlation did not reach statistical significance. The findings suggest that EDNRB gene expression analysis from blood samples using PCR has potential as a non-invasive biomarker to support early detection of Hirschsprung disease and provide insights into its pathogenesis. However, further studies with larger sample sizes are required to confirm its utility in severity assessment.  Keywords: Hirschsprung Disease, Endothelin B Receptors, Polymerase Chain Reaction, Biomarkers, Genetic, Early Detection of Cancer.